PD-L1 Testing for Urothelial Carcinoma: Interchangeability, Reliability and Future Perspectives - Gevaert, Thomas; Cimadamore, Alessia; Montironi, Rodolfo; Eckstein, Markus (Current Drug Targets, 2021)
Five programmed death-1/programmed death-ligand 1 (PD-L1) inhibitors are currently approved for the treatment of locally advanced or metastatic urothelial carcinoma of the bladder and the upper urinary tract. Following the FDA and EMA restrictions of first-line treatment with Atezolizumab and Pembrolizumab in platinum-ineligible patients, immunohistochemical PD-L1 testing is now required. Several emerging issues on antibodies, test platforms and scoring algorithms have raised concerns about the comparability and interchangeability between these assays. In this review, we have focused on the interchangeability of the used algorithms and assays for PD-L1 testing in urothelial carcinoma, on the predictive reliability of PD-L1 testing in urothelial carcinoma and the potential of other new and upcoming biomarkers.
CRIS-Team Scopus Importer:2021-03-19
Keywords: biomarker; immunohistochemistry; immunotherapy; interchangeability; PD-L1; urothelial carcinoma